Bacillus subtilis Fed to Sows Promotes Intestinal Development and Regulates Mucosal Immunity in Offspring - Liu, Peng; Zuo, Jinjiao; Lu, Hui; Zhang, Bin; Wu, Caihong (Veterinary sciences, 2025)
Diarrhea in piglets causes intestinal inflammation and epithelial damage. Weaned piglets fed with Bacillus subtilis (B.S) have enhanced intestinal mucosal immunity and reduces diarrhea in piglets. However, the immune system of newborn piglets is immature, and B.S cannot effectively activate the intestinal mucosal reaction when given directly. This research explored the impact of the maternal supplementation of B.S-Dia during the final 35 days of gestation on piglet intestinal development and mucosal immunity. The results demonstrated that B.S-Dia administration significantly increased the body weight, jejunal villus height, and crypt depth in the piglets. In addition, B.S-Dia also significantly increased the proliferative activity of intestinal epithelial cells, as evidenced by proliferating cell nuclear antigen (PCNA) staining and the elevated mRNA expression of the proliferation-related gene (c-Myc). Furthermore, B.S-Dia supplementation also reinforced the intestinal mucosal barrier by increasing goblet cell numbers and upregulating the mRNA expression of antimicrobial peptides, such as Muc2 and Lyz-1. Finally, elevated levels of IL-4 and IFN-γ, along with an increased abundance of CD3+ T cells, revealed that the intestinal mucosal immunity of piglets was improved after B.S-Dia administration. Our study indicates that feeding B.S-Dia to sow spromotes intestinal development and improves intestinal mucosal immunity in piglets.